ERS International Congress 2022: Highlights from the Allied Respiratory Professionals Assembly - Price, Oliver J (2023)
In this paper, we provide a brief overview of some of the outstanding sessions that were (co)organised by the Allied Respiratory Professionals Assembly during the 2022 European Respiratory Society (ERS) International Congress, which was held in a hybrid format. Early Career Members from Assembly 9 summarised the content of the sessions, with the support of the Officers from the four Assembly groups: Respiratory Function Technologists and Scientists (Group 9.01); Physiotherapists (Group 9.02); Nurses (Group 9.03); Psychologists and Behavioural Scientists (Group 9.04). The sessions covered the following topics: recent advances in cardiopulmonary exercise and challenge testing; the role and new trends in physiotherapy, exercise and physical activity promotion interventions in chronic respiratory diseases; development of the international curriculum for respiratory nurses and nursing aspects in disease management; and treatment adherence, e-health interventions and post Covid-19 challenges. This Highlights paper targets delegates who attended the Congress sessions, as well as those who were unable to attend, and provides valuable insight into the latest scientific data and emerging areas affecting the clinical practice of Allied Respiratory Professionals.